Strategy of Cell Group Multiplication in Church Planting Based on the Great Commission - Sonny Latuputty; Guntur Hari Mukti; Jovita Abraham (PT FORMOSA CENDEKIA GLOBAL, 2026)
Church planting in modern society faces serious challenges such as missionary growth stagnation and the tendency toward worship services and leadership figures that are centralized. This study aims to describe the theological basis of cell group multiplication based on the Great Commission and to analyze its implementation strategies in church planting. The research method used is qualitative with a library research approach, collecting and analyzing theological literature, scientific journals, and biblical studies systematically. The results show that the Great Commission in Matthew 28:19-20 gives a mandate for discipleship that is reproductive, while the pattern of the early church in Acts 2:42-47 demonstrates the effectiveness of house communities as a basis for growth and church planting. Effective cell group multiplication strategies include relational evangelism, reproductive discipleship, leadership multiplication, and the formation of new congregations.